2007
DOI: 10.1007/s11259-007-3468-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cadmium in Feed on Organs and Meat Colour of Growing Pigs

Abstract: One hundred and ninety-two barrows (Duroc x Landrace x Yorkshire, initial weight 27.7 kg) were used to investigate the effects of cadmium in feed on the function of selected organs and meat colour of growing pigs. The pigs were randomly allocated into four different treatments. Each treatment included three replications with 16 pigs per replicate. The animals were fed corn-soybean basal diet and supplemented with 0, 0.5, 5.0, 10.0 mg/kg cadmium (as CdCl(2)), respectively. The feeding trial ended when the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Horiguchi et al [16] observed hepatosplenomegaly and kidney swelling after subcutaneous administration of Cd in rats. Similarly, a Cd-induced increase in liver and spleen weight has also been observed by Tu et al [28].…”
Section: Cadmium Exposure Alters Oxidative Enzymes O R I G I N a L P supporting
confidence: 72%
“…Horiguchi et al [16] observed hepatosplenomegaly and kidney swelling after subcutaneous administration of Cd in rats. Similarly, a Cd-induced increase in liver and spleen weight has also been observed by Tu et al [28].…”
Section: Cadmium Exposure Alters Oxidative Enzymes O R I G I N a L P supporting
confidence: 72%
“…Cadmium (Cd), a nonessential element, can have various adverse effects on animals and humans because of its accumulation in the environment through the use of animal manures, phosphorus fertilizers, sewage sludge, or atmospheric deposition [19,20]. A high content of Cd may be present in livestock additives because of contamination of mineral supplements (e.g., some limestone added to laying hen feeds), which is excreted without any metabolization [21].…”
Section: Introductionmentioning
confidence: 99%
“…The cadmium concentrations in potato may be due to the soil in which the potato was grown (Bahemuka & Mubofu, 1999). In ice cream, a recent study suggested that the main inputs of cadmium to animal feed in farmed animals are feeding crops, trace element premixes, fish meal, and minerals such as, limestone and phosphate (Tu et al, 2007;Bilandzˇic´ et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%